The Effectiveness of Psychoeducation for Psychological Problems in Adolescents: A Systematic Literature Review - Rahadatul Aissy; Yoga Cahya Pangesta; Muslikah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Adolescence is a developmental phase vulnerable to various psychological problems due to complex emotional, social, and biological changes. Therefore, interventions are needed to help adolescents understand and manage their psychological conditions adaptively. This study aims to analyze the effectiveness of psychoeducational services in addressing psychological problems in adolescents through the Systematic Literature Review (SLR) method. The study was conducted following the Kitchenham protocol, which includes the stages of identification, selection, quality evaluation, and synthesis of article data. Literature searches were conducted through Google Scholar and Semantic Scholar databases with a publication range of 2016–2026. A total of 13 articles that met the inclusion criteria were analyzed using descriptive thematic analysis techniques to identify the form of intervention, type of psychological problem, implementation media, and the effectiveness of psychoeducational services. The results showed that psychoeducation is effective in reducing post-traumatic symptoms, addressing alexithymia, managing psychosomatic disorders, and preventing suicidal ideation in adolescents. In addition, school-based psychoeducation and digital platforms have been shown to increase the accessibility of mental health services. These findings confirm that psychoeducation is an important preventive and curative strategy in supporting the psychological well-being of adolescents.